Health-related quality of life after epilepsy surgery: A prospective, controlled follow-up on the Iranian population - Lotfinia, Mahmoud (Sci Rep, 2019)
Quality of life is affected by factors such as regional differences in access to treatment choices, and rehabilitation. This study aims to assess the result of epilepsy surgery and its impact on QoL in Iran. The data for 60 patients who underwent epilepsy surgery in Loghman-Hakim hospital between 2003 to 2017 were analyzed prospectively through clinical observation. Clinical variables of interest and the WHOQOL-BREF scale to assess QoL were applied. Scores of operated patients were compared to their preoperative scores as well as epileptic patients controlled with antiepileptic drugs (AEDs) and healthy individuals. The mean age of surgery group patients was 33.78 (34 male; 26 female). Twenty seven patients underwent temporal mesial lobectomy, 20 anterior callosotomy, and 13 neocortical resections. The average QoL score in healthy group was 72.48, in AEDs controls was 56.16, and in operated patients was 65.61. In addition, analysis showed a significant increase in postoperative QoL of the surgical group compared to the AEDs controls. Epilepsy surgery could be the best approach in patients suffering from drug-resistant epilepsy even in developing countries, which can result in seizure relief and a reduction in the frequency of disabling seizures.